HUBUNGAN KUALITAS PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN PENGGUNA BADAN PENYELENGARA JAMINAN SOSIAL KESEHATAN (BPJS) KESEHATAN DI RS JEMBER KLINIK - Said Mardjanto; Irwin Santoni (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2017)
The quality of health services is a basic thing that must be possessed by every health institution, in order to achieve good quality of service, each health event must pay attention to matters relating to customer needs. Health BPJS is a legal entity formed to hold health insurance. Patient satisfaction is a subjective value in the quality of services provided. Because good quality service will increase patient satisfaction. This study aims to determine the relationship of the quality of health services to patient satisfaction of users of BPJS HEALTH at Jember Hospital, Jember Clinic. The type of research used in this study was a survey with a cross sectional approach. The study population used accidental sampling of 40 respondents. Spearmen's Rho Correlation statistical test with significance level p <0.05. The results showed that the quality of health services with 72.5% satisfied criteria, 27.5% dissatisfied and 75.0% satisfied patients with satisfied criteria, 25.0% dissatisfied. Statistical test with Spearmen’s Rho Correlation produced correlation coefficient r = -356 with significance value p = 0.24. These results indicate that there is a relationship between the quality of health services and patient satisfaction of users of BPJS Health at Jember Hospital Jember Clinic, where the higher the quality of the services provided, the higher the patient's satisfaction will be. Patient satisfaction is supported by the respondent's perception that was felt during hospitalization at Jember Hospital Jember Clinic. It is expected that from this research the Hospital will improve the quality of health services to provide patient satisfaction